Weightbearing CT Scan Assessment of Foot Alignment in Patients With Hallux Rigidus. (January 2018) - Cheung, Zoe B.; Myerson, Mark S.; Tracey, Joseph; Vulcano, Ettore
Background: An association between hallux rigidus and metatarsus primus elevatus (MPE) has been suggested, although there remains no general consensus about the nature of this relationship. Past studies were limited due to inaccuracies of assessing MPE on 2-dimensional radiographs. The aims of this study were to (1) assess and compare foot alignment in patients with and without hallux rigidus using 3-dimensional (3D) reconstructions from weightbearing computed tomography (CT) and (2) assess intraobserver and interobserver reliability of these measurements. Methods: A prospective study was performed in 50 consecutive patients with symptomatic hallux rigidus and 50 control patients who underwent a weightbearing CT. Two investigators measured first and second metatarsal declination angles, first and second metatarsal lengths, first to second intermetatarsal angle (IMA), hallux valgus angle (HVA), and foot width on 3D CT reconstructions. Measurements were repeated after 1 month. Student t tests were performed to compare hallux rigidus and control groups. Intraclass and interclass correlation coefficients were calculated to evaluate reliability. Results: The first to second metatarsal declination ratio was less in patients with hallux rigidus (mean, 0.81) than controls (mean, 0.92; P < .001). Patients with Coughlin and Shurnas grade 3 and 4 hallux rigidus had greater first metatarsal declination than patients with grade 1 and 2 hallux rigidus. Last, IMA was higher (mean, 13 degrees) but HVA was lower (mean, 11 degrees) in patients with hallux rigidus than controls (IMA mean, 12 degrees; HVA mean, 15 degrees; P = .04). Intraobserver (ICC1, 1 ≥ 0.93) and interobserver (ICC3, 1 ≥ 0.85) reliability were good to excellent for all measured parameters. Conclusions: Patients with hallux rigidus had MPE. Patients with grade 3 and 4 hallux rigidus had more MPE than patients with grade 1 and 2 hallux rigidus. There was no clear correlation between hallux rigidus and bunions. Finally, weightbearing CT proved to be a reliable method of assessing all measured parameters. Level of Evidence: II, prospective comparative series.